2020
DOI: 10.1007/s10120-020-01066-4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting the GAS6/AXL axis suppresses tumor progression by blocking the interaction between cancer-associated fibroblasts and cancer cells in gastric carcinoma

Abstract: Background The effects of cancer-associated fibroblasts (CAF) on the progression of gastric carcinoma (GC) has recently been demonstrated. However, agents targeting the interaction between CAF and GC cells have not been applied in a clinical setting. Here, we examined if inhibition for Axl receptor tyrosine kinase (AXL) can suppress CAF-induced aggressive phenotype in GC. Methods We investigated the function of CAF-derived growth arrest-specific 6 (GAS6), a major ligand of AXL, on the migration and proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…For example, AXL induced the activation of downstream AKT, and inhibited the proliferation and migration of pancreatic cancer cells in vitro (29). In addition, GAS6 promoted gastric cancer invasiveness by activating AXL (30). Previous studies have demonstrated the role of AXL in regulating cell growth, migration and tumorigenesis of CRC cells (29,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, AXL induced the activation of downstream AKT, and inhibited the proliferation and migration of pancreatic cancer cells in vitro (29). In addition, GAS6 promoted gastric cancer invasiveness by activating AXL (30). Previous studies have demonstrated the role of AXL in regulating cell growth, migration and tumorigenesis of CRC cells (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…IHC analysis of ARL2 was performed on 19 colon cancer and 3 healthy colorectal tissues. The samples were fixed in 10% neutral buffered formalin for ~3-24 h at room temperature, dehydrated in gradient alcohol solution (30,50,70,80,90,95, 100, 100% alcohol each for 30 min) and paraffin-embedded. Paraffin-embedded tissues were cut into ~3-µm thick continuous sections.…”
Section: Methodsmentioning
confidence: 99%
“…Tumor metastasis is mainly caused by tumor cell migration and invasion [25][26][27]. Studies have shown that Gas6 and Axl are highly expressed in gastric, ovarian, and liver cancers, among many others, and patient prognosis is negatively correlated with Gas6/Axl complex levels [10,28,29]. Gas6/Axl can promote bone marrow and lung cancer metastasis and invasion as well as prostate cancer cell survival [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…In the tumor microenvironment, cancer-associated fibroblasts (CAFs) and CD45 + -expressing tumor-infiltrating leukocytes (TILs) also express Gas6 [ 69 , 70 , 71 , 72 ]. Among the TILs, macrophages and dendritic cells express high levels of Gas6 [ 71 , 72 ], which can be further promoted in these cell types by IL-10, M-CSF, and IFN⍺ [ 6 , 72 ].…”
Section: Gas6 and Axl Expression In The Tumor Microenvironmentmentioning
confidence: 99%
“…Although the mechanisms underlying Gas6 upregulation in TILs is not fully understood, in vitro studies demonstrate that tumor cells or tumor cell conditioned media induce Gas6 expression and secretion in macrophages [ 71 , 73 ]. Gomes and colleagues showed that stromal cell-derived Gas6 promotes tumor cell migration, invasion, survival, and proliferation [ 70 , 71 ]. Potential downstream effectors of the Gas6/Axl signaling through macrophage-derived Gas6 include pAkt and pStat3 [ 64 , 71 ].…”
Section: Gas6 and Axl Expression In The Tumor Microenvironmentmentioning
confidence: 99%